Supported self-management for patients with COPD who have recently been discharged from hospital: a systematic review and meta-analysis - Majothi S; Jolly K; Heneghan NR; Price MJ; Riley RD; Turner AM; Bayliss SE; Moore DJ; Singh SJ; Adab P; Fitzmaurice DA; Jordan RE (International Journal of COPD, 2015)
Saimma Majothi,1 Kate Jolly,1 Nicola R Heneghan,2 Malcolm J Price,1 Richard D Riley,3 Alice M Turner,4 Susan E Bayliss,1 David J Moore,1 Sally J Singh,5 Peymané Adab,1 David A Fitzmaurice,6 Rachel E Jordan1 1Public Health, Epidemiology and Biostatistics, School of Health and Population Sciences, University of Birmingham, Birmingham, UK; 2School of Sport, Exercise and Rehabilitation Sciences, University of Birmingham, Birmingham, UK; 3Research Institute of Primary Care and Health Sciences, Keele University, Staffordshire, UK; 4Queen Elizabeth Hospital Research Laboratories, Birmingham, UK; 5Centre for Exercise and Rehabilitation Science, University Hospitals of Leicester NHS Trust, Glenfield Hospital, Leicester, UK; 6Primary Care Clinical Sciences, School of Health and Population Sciences, University of Birmingham, Birmingham, UK Purpose: Although many hospitals promote self-management to chronic obstructive pulmonary disease (COPD) patients post discharge from hospital, the clinical effectiveness of this is unknown. We undertook a systematic review of the evidence as part of a Health Technology Assessment review.Methods: A comprehensive search strategy with no language restrictions was conducted across relevant databases from inception to May 2012. Randomized controlled trials of patients with COPD, recently discharged from hospital after an acute exacerbation and comparing a self-management intervention with control, usual care or other intervention were included. Study selection, data extraction, and risk of bias assessment were undertaken by two reviewers independently. Results: Of 13,559 citations, 836 full texts were reviewed with nine randomized controlled trials finally included in quantitative syntheses. Interventions were heterogeneous. Five trials assessed highly supported multi-component interventions and four trials were less supported with fewer contacts with health care professionals and mainly home-based interventions. Total sample size was 1,466 (range 33–464 per trial) with length of follow-up 2–12 months. Trials varied in quality; poor patient follow-up and poor reporting was common. No evidence of effect in favor of self-management support was observed for all-cause mortality (pooled hazard ratio =1.07; 95% confidence interval [0.74 to 1.55]; I2=0.0%, [n=5 trials]). No clear evidence of effect on all-cause hospital admissions was observed (hazard ratio 0.88 [0.61, 1.27] I2=66.0%). Improvements in St George’s Respiratory Questionnaire score were seen in favor of self-management interventions (mean difference =3.84 [1.29 to 6.40]; I2=14.6%), although patient follow-up rates were low.Conclusion: There is insufficient evidence to support self-management interventions post-discharge. There is a need for good quality primary research to identify effective approaches. Keywords: chronic obstructive pulmonary disease, self-management support, post-discharge, systematic review